Implementation of “Do Not Resusitate (DNR)” In Indonesia's Law and the Study of Ethical Principles of Their Implementation - Kadek Radhitya Vidianditha; I Nyoman Bagiastra; Ria Tri Harini Dwi Rusiawati (Budapest International Research and Critics University, 2022)
This study aims to analyze and examine in depth the implementation of the